Design of 4π Directional Radiation Detector based on Compton Scattering Effect - Max Ghelman (EDP Sciences, 2021)
Obtaining directional information is required in many applications such as nuclear homeland security, contamination mapping after a nuclear incident and radiological events, or during the decontamination work. However, many directional radiation detectors are based on directional shielding, made of lead or tungsten collimators, introducing two main drawbacks. The first is the size and weight, making those detectors too heavy and irrelevant for utilization in handheld devices, drone mapping, or space applications. The second drawback is the limited field of view, which requires multiple detectors to cover the whole required field of view or machinery to rotate the narrow field of view detector. We propose a novel 4π directional detector based on a segmented hollow cubic detector, which uses the Compton effect interactions with no heavy collimators. The symmetrical cubical design provides both higher efficiency and 4π detection ability. Instead of traditional two types of detectors (scatterer and absorber) structure, we use the same type of detector, based on GAGG(Ce) scintillator coupled to silicon photomultiplier. Additional advantage of the proposed detector obtained by locating the photon sensors inside the detector, behind the scintillators, which improves the radiation hardness required for space applications. Furthermore, such arrangement flattens the temperature variation across the detector, providing better gain stability. The main advantage of the proposed detector is the ability of 4pi radiation detection for high energy gamma-rays without the use of heavy collimators.